LEARNING MEDIA DESIGN BASED ON THE ANDROID PSR 12 APPLICATION IN THE ROBOTIC SYSTEM CONTROL SUBJECT - Annisa, Nurul Sahidati; Rusmono; Jusuf Bintoro (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2024)
This study aims to develop learning media based on the Android PSR 12 application in the Robotic System Controller subject for class XII students of Industrial Electronics Engineering and to test the feasibility level based on material experts, media experts, instructional design experts and class XII TEI students of SMKN 5 Kota Bekasi. The research method used in this study is the Research and Development (R&D) method with the ADDIE development model which is limited to three stages, namely Analyze, Design and Development. The final product produced is an Android PSR 12 application that has been validated by media experts, instructional design experts and material experts. The results of the feasibility test by the instructional design experts obtained a percentage of 95%. The results of the feasibility test by the media experts obtained a percentage of 82.7%. The results of the feasibility test by the material experts obtained a percentage of 90%. The assessment by students in individual trials obtained a score of 89.1% and in small group trials obtained a percentage of 87.6%. So based on the feasibility category, it can be concluded that the Android application-based learning media PSR 12 is categorized as very suitable for use as a learning medium.